Terpenoids and Their Biosynthesis in Cyanobacteria - Pattanaik, Bagmi (Life (Basel), 2015)
Terpenoids, or isoprenoids, are a family of compounds with great structural diversity which are essential for all living organisms. In cyanobacteria, they are synthesized from the methylerythritol-phosphate (MEP) pathway, using glyceraldehyde 3-phosphate and pyruvate produced by photosynthesis as substrates. The products of the MEP pathway are the isomeric five-carbon compounds isopentenyl diphosphate and dimethylallyl diphosphate, which in turn form the basic building blocks for formation of all terpenoids. Many terpenoid compounds have useful properties and are of interest in the fields of pharmaceuticals and nutrition, and even potentially as future biofuels. The MEP pathway, its function and regulation, and the subsequent formation of terpenoids have not been fully elucidated in cyanobacteria, despite its relevance for biotechnological applications. In this review, we summarize the present knowledge about cyanobacterial terpenoid biosynthesis, both regarding the native metabolism and regarding metabolic engineering of cyanobacteria for heterologous production of non-native terpenoids.